Extracting mode shapes for beams through a passing auxiliary mass - Zhang, Yao (2019)
This paper shows an approach to evaluate mode shapes for beams through using a passing auxiliary mass. The coupled system of an auxiliary mass passing over a beam is time-dependent, and the corresponding instantaneous frequencies (IFs) are equivalent to the mode shapes. Hence, reconstruction of the mode shapes is easy to be achieved through estimating the IFs. A simple algorithm based on ridge detection is proposed to reconstruct the mode shapes. This method is effective if the beam is light or the lumped mass is heavy. It is convenient since it requires an accelerometer mounted on the passing auxiliary mass rather than a serious of sensors mounted on the structure itself. It is also more practical because it is usually difficult to install external exciter. A lab-scale experimental validation shows that the new technique is capable of identifying the first three mode shapes accurately.